Discourse Analysis on Prime Minister of Lebanon Sa’ad Al-Hariri’s Resignation Speech - Setianingsih, Yuli; Muta'ali, Abdul (Proceedings of AICS - Social Sciences, 2018)
This study is established on Sa’ad Al-Hariri’s resignation speech as Prime Minister of Lebanon on 04 November 2017. In his speech, there are utterly meaningful utterances and redactions to be studied in terms of semantics and pragmatics. This study aims to analyse how the semantic form and pragmatic speech of acts contained in Sa'ad Al-Hariri's speech. This study uses the approach of Critical Discourse Analysis model of Norman Fairclough, 1995 and Theory of Speech Acts of Searle, 1979. The data contained in this research is sourced from mass media of Al-Jazeera online newspaper, literature readings, articles, and some documents from mass media. The method used in writing this article is qualitative method with descriptive approach. From the results of data analysis, there are several propositions which show that in Sa'ad Al-Hariri's speech, although he resigned, the editorial is quite declarative at the same time. Additionally, in his speech he revealed the reasons for his resignation and also appealed to the Lebanese people to support him. This research is expected to be a reference for other researchers whose interest in the field of discourse analysis and speech acts or from other relevant disciplines.Keywords:critical discourse analysis, acts of speech, Sa’ad Al-Hariri, Lebanon.